Integrating Spiritual and Ecological Education in Early Childhood through an Outing Class Program at RA Yaa Bunayya Papua - Talabudin Umkabu; A Ubaidillah; Sulis Maryati (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This study aims to analyze spiritual and ecological education for early childhood through an outing class program at RA Yaa Bunayya. The research employed a descriptive qualitative approach with a case study design, involving semi-structured interviews, participatory observation, and documentation as data collection techniques. Data were analyzed through data reduction, data presentation, and drawing conclusions, with source and method triangulation to ensure validity. The findings indicate that the outing class effectively instills spiritual values through the appreciation of Allah’s creations and fosters ecological awareness through hands-on plant care activities. The program also enhances contextual learning, develops social character, independence, and responsibility, while introducing children to the functions of government institutions, community professions, and modes of transportation. These results suggest that outing classes serve as a holistic, engaging, and effective learning strategy for cultivating early childhood individuals who are faithful, environmentally conscious, and responsible.